1994
DOI: 10.1111/j.1365-2265.1994.tb02528.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression patterns of messenger ribonucleic acids encoding prohormone convertases (PC2 and PC3) in human pituitary adenomas

Abstract: The expression of PC2 and PC3 mRNA in human pituitaries has been confirmed. However, their expression has been observed to vary quantitatively and not to be restricted to certain types of pituitary cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Indeed, Righi et al, studying a series of functioning and silent CTs, reported that the three cases of silent CTs that evolved during follow-up to functioning ones showed an increase in PCSK1 and PC1/3 expression (9). Regarding ACTH post-translation regulation, most authors have reported a decrease in ACTH degradation in CT tumors compared with other PitNET subtypes, without differences between functioning and silent CTs (12,29). Our data agree with those previously reported, showing lower PCSK2 and PC2 expressions in functioning and silent CTs than in silent GTs.…”
Section: Intermediate State Between Micro-functioning and Silentsupporting
confidence: 92%
“…Indeed, Righi et al, studying a series of functioning and silent CTs, reported that the three cases of silent CTs that evolved during follow-up to functioning ones showed an increase in PCSK1 and PC1/3 expression (9). Regarding ACTH post-translation regulation, most authors have reported a decrease in ACTH degradation in CT tumors compared with other PitNET subtypes, without differences between functioning and silent CTs (12,29). Our data agree with those previously reported, showing lower PCSK2 and PC2 expressions in functioning and silent CTs than in silent GTs.…”
Section: Intermediate State Between Micro-functioning and Silentsupporting
confidence: 92%
“…In the present immunohistochemical study, we showed that expression of PC1/3 protein was negative in all 6 SCA tissues in contrast to the positive PC1/3 immunoreactivity in an ACTH-secreting pituitary tumor causing clinically overt Cushing's disease. PC1/3 is responsible for proper processing of POMC into mature ACTH(1-39) in a tissue-specific fashion [11,12,13], and highly expressed in ACTH-secreting adenomas [14,15]. However, there have been few studies on PC1/3 expression in SCA thus far reported; one case with negative PC1/3 expression [16], and another case with positive PC1/3 expression [8].…”
Section: Discussionmentioning
confidence: 99%
“…Prohormone convertase (PC) 3 was later indicated to be the same as PC 1 and now is designated as PC1/3. In endocrine tumors, the functions of PC1/3 and PC2, which are present in the neuroendocrine tissues, have been the subject of several investigations (Bloomquist et al 1991;Ohagi et al 1992;Seidah and Chretien 1992;Hashimoto et al 1994;Scopsi et al 1995;. Morphological studies have been done in pancreatic and pituitary tumors Otoh et al 1996).…”
Section: Processing Of Prohormonesmentioning
confidence: 99%